2016
DOI: 10.1080/15476286.2016.1201617
|View full text |Cite
|
Sign up to set email alerts
|

RNA-based mechanisms of virulence control in Enterobacteriaceae

Abstract: Enteric pathogens of the family Enterobacteriaceae colonize various niches within animals and humans in which they compete with intestinal commensals and are attacked by the host immune system. To survive these hostile environments they possess complex, multilayer regulatory networks that coordinate the control of virulence factors, host-adapted metabolic functions and stress resistance. An important part of these intricate control networks are RNA-based control systems that enable the pathogen to fine-tune it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 146 publications
(200 reference statements)
0
21
0
Order By: Relevance
“…Transcription of the genes for the glycine betaine ABC transporter, proVWX (43), also increased 4-fold, suggesting that the lipid-rich environment of lung surfactant invokes osmotic stress in K. pneumoniae. Two tRNA nucleotide modification enzymes were also induced under these conditions, with queC and gidA exhibiting 5.4-and 2.8-fold increases in transcript abundance, respectively (44,45). Finally, transcription of genes associated with antibiotic resistance were also upregulated, including the genes for the 23S rRNA methylation enzyme (yfgB) and aminoglycoside 3=-phosphotransferase (strB) (2.6-to 2.7-fold increase) (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…Transcription of the genes for the glycine betaine ABC transporter, proVWX (43), also increased 4-fold, suggesting that the lipid-rich environment of lung surfactant invokes osmotic stress in K. pneumoniae. Two tRNA nucleotide modification enzymes were also induced under these conditions, with queC and gidA exhibiting 5.4-and 2.8-fold increases in transcript abundance, respectively (44,45). Finally, transcription of genes associated with antibiotic resistance were also upregulated, including the genes for the 23S rRNA methylation enzyme (yfgB) and aminoglycoside 3=-phosphotransferase (strB) (2.6-to 2.7-fold increase) (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the observed result in the GUS quantitative assay was based on enzyme accumulation during bacterial growth, while qRT-PCR result reflected an instantaneous bacterial state at a given assay time. Likewise, it is possible that many plant-regulated genes in D. solani are controlled by so-called short lived transcripts ( Heroven et al, 2017 ) and, again, these genes could be found differentially induced as measured by both methods (GUS expression and qRT-PCR).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RNA-seq has permitted the identification of sensory RNA elements and numerous noncoding RNAs (ncRNAs) in pathogenic bacteria. A small subset of the few already characterized riboregulators was found to contribute to pathogenesis (1)(2)(3).…”
mentioning
confidence: 99%